Medicaid expansion is associated with a higher likelihood of early diagnosis, resection, transplantation, and overall survival in patients with hepatocellular carcinoma. Issue 9 (September 2022) - Elshami, Mohamedraed; Hoehn, Richard; Hue, Jonathan J.; Rothermel, Luke; Chavin, Kenneth D.; Ammori, John B.; Hardacre, Jeffrey M.; Winter, Jordan M.; Ocuin, Lee M.
Abstract: Background: We examined the association between Medicaid expansion (ME) and the diagnosis, treatment, and survival of patients with hepatocellular carcinoma (HCC). Methods: We identified patients with HCC <65yrs with Medicaid or without insurance within the National Cancer Database before (2010–2013) or after (2015–2017) ME with early (cT1) or intermediate/advanced (cT2-T4 or M1) disease. Results: We identified 4848 patients with HCC before and 4526 after ME. Prior to ME, there was no association between future ME status and diagnosis of early HCC (34.5% vs. 32.9%). There was no association between future ME status and treating early HCC with ablation, resection, or transplantation. Patients with early HCC in future ME states were less likely to die (HR = 0.81, 95% CI: 0.67–0.98). After ME, patients in ME states were more likely to be diagnosed with early HCC (39.2% vs. 32.1%). Patients with early disease in ME states were more likely to undergo resection (OR=1.78, 95% CI: 1.16–2.75) or transplantation (OR=3.20, 95% CI: 1.40–7.33). There was a further associated decrease in the hazard of death (HR=0.68, 95% CI: 0.54–0.86). Conclusion: ME was associated with early diagnosis of HCC. For early HCC, ME was associated with increased utilization of resection and transplantation and improvement in survival.